2007
DOI: 10.1159/000102096
|View full text |Cite
|
Sign up to set email alerts
|

Nucleated Red Blood Cells in Term Fetuses: Reference Values Using an Automated Analyzer

Abstract: Background: Nucleated red blood cells (NRBCs) are present in small numbers in the cord blood of healthy fetuses at birth. Acute and chronic stimuli, such as fetal hypoxia, cause increased circulating levels of NRBCs. Manual counting is presently the only way to quantify NRBCs, but it is time-consuming and inaccurate. Recently, automated approaches have been developed in order to quantify NRBCs. Objectives: Our aim was to compare manual vs. automated NRBC counting and derive reference values in umbilical cord b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 37 publications
2
11
0
Order By: Relevance
“…58 However, at term nucleated red blood cells comprise a small percentage of total cell number (3 per 100 wbcs), which limits their influence on the methylation of cells from cord blood. 59 Furthermore, according to the Marmal-aid data set, we showed a similar pattern of DMPs in areas normally unmethylated and across cord blood cell types. Differences in cell type that might exist at term between FGR and AGA are unlikely to play a significant role in observed DMPs.…”
Section: Gobpidmentioning
confidence: 55%
“…58 However, at term nucleated red blood cells comprise a small percentage of total cell number (3 per 100 wbcs), which limits their influence on the methylation of cells from cord blood. 59 Furthermore, according to the Marmal-aid data set, we showed a similar pattern of DMPs in areas normally unmethylated and across cord blood cell types. Differences in cell type that might exist at term between FGR and AGA are unlikely to play a significant role in observed DMPs.…”
Section: Gobpidmentioning
confidence: 55%
“…This is the same conclusion reached by Perrone et al [1] . Rolfo et al [3] found no difference between automated and manual NRBC counts of 50 neonatal samples. Similarly, Gulati et al [10] studied 460 samples of adult blood, and generally found agreement between automated and manual methods.…”
Section: Discussionmentioning
confidence: 93%
“…Nucleated red blood cells (NRBC) are often observed in the blood of term and preterm neonates [1][2][3] . A high concentration of NRBC at birth has been associated with an increased risk of developing intraventricular hemor-290 rhage (IVH) and/or retinopathy of prematurity (ROP) [4,5] .…”
Section: Introductionmentioning
confidence: 99%
“…2 ). Based on the upper limit of normal NRBC values (above the 97.5th percentile) published in the literature [6,7] , 5/6 (83%) group 1 patients compared with 3/14 (21%) group 2 patients had NRBC counts above the upper reference limit ( fig. 3 ).…”
Section: Resultsmentioning
confidence: 99%